A SCOPING REVIEW: PEMETAAN BUKTI HUBUNGAN MASA KERJA DAN TINGKAT KEPUASAN PERAWAT DALAM PENGGUNAAN ELECTRONIC MEDICAL RECORD - Makarewa, Grace Christy Melinda; Mambu, Ian Ruddy (Klabat Journal of Nursing, 2025)
The implementation of Electronic Medical Records (EMR) has become an essential component of the digital transformation of healthcare services. However, nurses’ dissatisfaction as primary users can negatively impact documentation quality, work efficiency, and the overall success of system adoption. This scoping review aims to map the scientific evidence regarding the relationship between nurses’ length of service and their satisfaction with EMR use in various healthcare settings. This review employed the Joanna Briggs Institute (JBI) methodology and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines. Literature searches were conducted in PubMed, ScienceDirect, and SpringerLink, with a descriptive thematic analysis approach. Nine quantitative articles were included. The mapping results indicate that nurses with less than five years of experience tend to have a more positive perception of EMR. Identified advantages of EMR include improved documentation efficiency, faster data access, and enhanced clinical decision support, while drawbacks include increased administrative burden, limited training, and technical challenges. Organizational factors such as system design quality, managerial support, and digital readiness also influence nurses’ satisfaction. These findings map current empirical evidence while highlighting research gaps, emphasizing that length of service is an important but not the sole determinant. Adaptive EMR implementation strategies that consider work experience, user needs, and institutional conditions are essential to enhance satisfaction and ensure successful system adoption. Implementasi Electronic Medical Record (EMR) telah menjadi komponen esensial dalam transformasi digital layanan kesehatan. Namun, ketidakpuasan perawat sebagai pengguna utama dapat berdampak pada kualitas dokumentasi, efektivitas kerja, dan keberhasilan adopsi sistem. Scoping review ini bertujuan untuk memetakan bukti ilmiah terkait hubungan masa kerja perawat dan tingkat kepuasan penggunaan EMR di berbagai konteks pelayanan kesehatan. Tinjauan ini menggunakan metode Joanna Briggs Institute (JBI) dan pelaporan mengikuti pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR). Pencarian dilakukan pada PubMed, ScienceDirect, dan SpringerLink, dengan analisis deskriptif tematik. Sembilan artikel kuantitatif terinklusi. Hasil pemetaan menunjukkan bahwa perawat dengan masa kerja kurang dari lima tahun cenderung memiliki persepsi yang lebih positif terhadap EMR. Kelebihan EMR yang diidentifikasi meliputi peningkatan efisiensi dokumentasi, akses data yang lebih cepat, dan dukungan pengambilan keputusan klinis, sedangkan kelemahannya mencakup beban administratif tambahan, keterbatasan pelatihan, dan kendala teknis. Faktor organisasi seperti kualitas desain sistem, dukungan manajerial, dan kesiapan digital juga memengaruhi kepuasan perawat. Temuan ini memetakan bukti empiris terkini sekaligus mengidentifikasi kesenjangan penelitian, menekankan bahwa masa kerja merupakan faktor penting tetapi bukan satu-satunya determinan. Strategi implementasi EMR yang adaptif terhadap pengalaman kerja, kebutuhan pengguna, dan kondisi institusional diperlukan untuk meningkatkan kepuasan dan keberhasilan adopsi sistem.